Sistem Pendukung Keputusan Dalam Menentukan Pemain Basket Terbaik Menggunakan Algoritma Analytical Hierarchy Process (AHP) (Study Kasus Klub Angsapura Sania Medan) - Berto Nadeak; Setyawati Arbaatun; Fadlina Fadlina (JURIKOM (Jurnal Riset Komputer), 2018)
Basketball is a ball game in groups. Consisting of two teams consisting of five people who competed each other scored points by inserting an opponent's ball. The movement consists of a combination of elements that are coordinated neatly so as to play the ball well. In basketball training at KlubAngsapura Sania Medan, there are several things that are done to determine the player that is dribbling, shooting, passing, agility. The activity is done regularly and recorded manually on a notebook, either by coach or assistant coach. Problems arise when many players have to be selected, making it difficult for the coach to determine the player's election. Because it requires a decision support application so that the coach can evaluate the team's performance and make decisions so that the bias applies the appropriate strategy. This application is capable of giving statistic of player development. The method used is Analytical Hierarchy Process (AHP) method, where Analytical Hierarchy Process (AHP) method compares the best aspect with existing player aspect.